1975
DOI: 10.1084/jem.141.5.1030
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine effects on lysosomal enzyme induction and intracellular degradation in the cultivated macrophage.

Abstract: The effects of colchicine on lysosomal fusion and lysosomal enzyme induction in the cultivated mouse peritoneal macrophage have been examined. Colchicine (10- minus 6 M), but not lumicolchicine, inhibited lysosomal enzyme induction by both phagocytic and pinocytic stimuli. In addition, the drug significantly retarded pinocytic uptake of [3-H] sucrose and transport of the amino acids [3-H] alpha aminoisobutyric acid and L-[3-H] leucine. In contrast, lumicolchicine had no effect on pinocytosis or amino acid tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
2

Year Published

1976
1976
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(28 citation statements)
references
References 34 publications
(44 reference statements)
1
25
2
Order By: Relevance
“…It has been hypothesized that microtubules are important for the secretion of lysosomal enzymes and the intracellular degradation of materials phagocytosed by macrophages [107] . It has also been suggested that microtubules are necessary for the fusion of lysosomes with endosomes which must precede intracellular digestion of phagocytosed materials [108] , whereas others have reported that intact microtubules are not required for the lysosomal-endosomal fusion [109] . We found that the mitotic activity of AMC was suppressed by colchicine, but the phagocytic activity remained unaffected [103] .…”
Section: Response To Drugsmentioning
confidence: 99%
“…It has been hypothesized that microtubules are important for the secretion of lysosomal enzymes and the intracellular degradation of materials phagocytosed by macrophages [107] . It has also been suggested that microtubules are necessary for the fusion of lysosomes with endosomes which must precede intracellular digestion of phagocytosed materials [108] , whereas others have reported that intact microtubules are not required for the lysosomal-endosomal fusion [109] . We found that the mitotic activity of AMC was suppressed by colchicine, but the phagocytic activity remained unaffected [103] .…”
Section: Response To Drugsmentioning
confidence: 99%
“…Colchicine has little effect for several hours on total protein synthesis in the macrophage (16), but the species formed could be substantially modified in the presence of colchicine (13). The continued accumulation of Although a direct effect on microtubules has not been demonstrated in these studies, morphologic evidence suggests that modification of enzyme secretion by colchicine and related agents occurs in parallel with depolymerization of macrophage microtubules (11,16). The efficacy of low doses of colchicine and inactivity of lumicolchicine are also consistent with such a relationship (9).…”
Section: Effect Of Cytochalasin Bmentioning
confidence: 99%
“…The constant concentration found during the whole period of infection may reflect an equilibrium between steady multiplication and death. If so, then colchicine-which interferes with the cellular regulation but has little effect on phagocytosis (Malawista and Bodel, 1967;Pesanti and Axline, 1975)-should be able to disrupt this chronic equilibrium. This prediction was confirmed.…”
Section: Figmentioning
confidence: 99%